sophiahunt
sophiahunt
16-02-2018
Mathematics
contestada
For f(x) =2x+1 and g(x)=x^2-7, fine (f*g)(x)
Respuesta :
texaschic101
texaschic101
16-02-2018
(f * g)(x)
(2x + 1)(x^2 - 7) =
2x(x^2 - 7) + 1(x^2 - 7) =
2x^3 - 14x + x^2 - 7 =
2x^3 + x^2 - 14x - 7 <===
Answer Link
VER TODAS LAS RESPUESTAS ( 34+ )
Otras preguntas
Translate the following sentence into an equation. Subtracting 5 from the quotient of a number and 6 gives 37.
During his tennis career in singles play, John won 3 fewer tournament A titles than tournament B titles, and 2 more tournament C titles than tournament B titles
differentiate between plant cell and animal cell prokaryotic cell eukaryotic cell
The running time for movie A is 33 mins more than twice the running time for movie B. If the running time for movie A is subtracted from triple the running time
Translate the following sentence into an equation. Subtracting 5 from the quotient of a number and 6 gives 37.
inequalities x+3 <=10
name five states formed from thd old northwest territory
Fitness can be achieved only through ?
want a telugu poem on truth
What factors slow down economic development of US?